2015
DOI: 10.1111/1365-2745.12370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seagrass loss and subsequent revegetation on carbon sequestration and stocks

Abstract: Summary1. Seagrass meadows are sites of high rates of carbon sequestration and they potentially support 'blue carbon' strategies to mitigate anthropogenic CO 2 emissions. Current uncertainties on the fate of carbon stocks following the loss or revegetation of seagrass meadows prevent the deployment of 'blue carbon' strategies. 2. Here, we reconstruct the trajectories of carbon stocks associated with one of the longest monitored seagrass restoration projects globally. We demonstrate that sediment carbon stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
152
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 23 publications
7
152
0
2
Order By: Relevance
“…Likewise, global losses of seagrass meadows (Orth et al, 2006;Waycott et al, 2009) may have impacted on their contribution to carbon sequestration in bare sediments elsewhere. The consequences of seagrass loss for the capacity of seagrass meadows to sequester and store organic carbon have been assessed on the basis of the impacts on sediment organic carbon stocks and fluxes in the meadows (e.g., Fourqurean et al, 2012;McGlathery et al, 2012;Duarte et al, 2013;Marba et al, 2015). However, the finding that seagrasses act as significant sources of organic carbon to sediments beyond the meadows, extending to the hadal zone of the deep sea, indicates that the consequences of continuing seagrass decline extend far beyond the areas where seagrasses grow (Heck et al, 2008).…”
Section: Sequestration Of Seagrass Carbon In Coastal Sediments Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, global losses of seagrass meadows (Orth et al, 2006;Waycott et al, 2009) may have impacted on their contribution to carbon sequestration in bare sediments elsewhere. The consequences of seagrass loss for the capacity of seagrass meadows to sequester and store organic carbon have been assessed on the basis of the impacts on sediment organic carbon stocks and fluxes in the meadows (e.g., Fourqurean et al, 2012;McGlathery et al, 2012;Duarte et al, 2013;Marba et al, 2015). However, the finding that seagrasses act as significant sources of organic carbon to sediments beyond the meadows, extending to the hadal zone of the deep sea, indicates that the consequences of continuing seagrass decline extend far beyond the areas where seagrasses grow (Heck et al, 2008).…”
Section: Sequestration Of Seagrass Carbon In Coastal Sediments Beyondmentioning
confidence: 99%
“…Remedial actions to reduce nutrient inputs in Denmark and elsewhere have been shown to lead to eelgrass recovery (Riemann et al, 2016) and seagrass planting programs are likely to contribute to rebuild these carbon stocks (e.g., McGlathery et al, 2012;Marba et al, 2015). However, assessment of carbon budgets in seagrass sediments have shown that older meadows export more material than younger ones (Cebrián et al, 2000), so that compensatory planting programs would not compensate for previous losses until the meadows reach a mature state.…”
Section: Sequestration Of Seagrass Carbon In Coastal Sediments Beyondmentioning
confidence: 99%
“…Clearly, in order to produce more reliable estimates of global seagrass carbon sequestration rates and stocks, there is a need for more studies integrating and modelling the individual and joint role of, for example, sediment biogeochemistry, seascape structure, plant species architecture and hydrodynamic regime. Since seagrasses are lost at accelerating rates (Waycott et al, 2009), there is also an urgent need for a better understanding of the fate of lost seagrass carbon (Macreadie et al, 2014) and the development of the carbon sink capacity in restored seagrass ecosystems (Nellemann et al, 2009;Greiner et al, 2013;Marba et al, 2015). Nelleman et al (2009) proposed the use of carbon trading programmes using financial incentives for forest conservation, such as REDD+ (Reduced Emissions from Deforestation and Degradation) and NAMAs (nationally appropriate mitigation actions), to include the blue carbon ecosystems as part of their environmental protection protocol.…”
Section: Consequences Of Seagrass Loss For Carbon Poolsmentioning
confidence: 99%
“…The 'blue carbon' sequestration capacity of seagrass meadows may be lost with habitat degradation worldwide (Pendleton et al 2012), but restoration can reinstate this important ecosystem service (McGlathery et al 2012, Greiner et al 2013, Marbà et al 2015. In the Virginia coastal bays, a rapid increase in shoot density oc curred 4 yr after seeding (McGlathery et al 2012), and, after approximately 5 yr, the restored seagrass meadow began to accumulate measurable carbon in the sediment (Greiner et al 2013).…”
Section: Carbon Accumulation and Sourcesmentioning
confidence: 99%
“…The accumulation of carbon in coastal ecosystems, termed 'blue carbon', is a means of mitigating climate change and increased atmospheric carbon dioxide levels (Nellemann et al 2009, Mcleod et al 2011, Duarte et al 2013b). The enhancement of 'blue carbon' sequestration is possible through the restoration of seagrass meadows (Greiner et al 2013, Marbà et al 2015.…”
Section: Introductionmentioning
confidence: 99%